Pemodelan Indeks Harga Saham pada Jakarta Islamic Index Menggunakan Generalisasi Proses Wiener - ike mairita sari; media rosha (Journal of Mathematics UNP, 2019)
Abstract–Investment is a commitment to a number of funds or other resources carried out at this time with the aim of obtaining future profits. There are two types of investment, namely investment in real assets and investing in financial assets. Shares are instruments in the capital market that are often used by investors. Stock prices that change from time to time are very influential for shareholders. The purpose of this research is to form a stock price movement formula using the Wiener process method. The steps taken in this study are to form a model and make predictions. The results of this study obtained a mathematical model of stock price movements as well as stock price predictions for the 26 future periods. The results show that the highest and lowest share prices each occur on November 19, 2018 and November 16, 2018, with a prediction error value of 5,26581%.Keywords–Stock Price, Wiener Process, Jakarta Islamic Index.